POLYGAMY IN MINANGKABAU TAFSIR: A COMPARATIVE STUDY OF THE THOUGHTS OF SULAIMAN AR-RASULI AND BUYA HAMKA - Shofa, Ida Kurnia; Chairinisa, Putri Evta (UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
This writing will discuss how QS An-Nisa verse 3 is understood by two modern Minangkabau scholars who are different, namely Syeikh Sulaiman Ar-Rasuli and Buya Hamka. The purpose of this research is to find out the differences in the interpretation of these two scholars, who each have different socio-historical backgrounds. This research is a library research using comparative analysis method and sociological approach. The results show that there is a difference in the interpretation of polygamy by these two scholars. Syeikh Sulaiman Ar-Rasuli tends to connect the text with the cultural context in society, while Buya Hamka prefers to criticize culture in his interpretation. This is caused by several factors, including the personal experiences of each scholar. In addition, Ar-Rasuli is a polygamist, while Hamka does not do it due to personal experience related to his parents' marriage.